Pengaruh Teeamwork. Semangat Kerja, Dan Loyalitas Kerja Terhadap Produktivitas Karyawan (Studi Kasus Pada Karyawan Perusahaan Konveksi Manfaat - Satria Sabilillah; Budi Wahono; M. Khoirul Anwarodin Broto. S (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract This research was conducted at the “Manfaat” Convection Company in Ngunut District, Tulungagung Regency. this company is one of the service businesses engaged in convection and embroidery. The purpose of the study was to determine whether teamwork, work spirit and work loyalty had an effect on employee productivity at a benefit convection company. The type of research used was quantitative research with questionnaire distribution method. The sample in this study were 36 respondents and data processing using SPSS computer program. The variable used in this study is productivity (dependent variable), while the independent variables are teamwork, work spirit and work loyalty. This study has met the requirements of validity and reliability. Analysis of the data used in this study is the classical assumption test, multiple linear regression, hypothesis testing and analysis of the coefficient of determination. The results of this study conclude that the variables of Teamwork, Morale and Work Loyalty have an effect either simultaneously or partially on Employee Work Productivity. For the Manfaat convection company, it is necessary to maintain teamwork, work spirit, and work loyalty because all these variables have very good values, so Companies must maintain the quality of employees that have been done so far in increasing work productivity and also the company. Keywords: Teamwork, Work Spirit, Work Loyalty, Productivity.